Artificial insemination unveils a first-male fertilization advantage in the guppy. (September 2017) - Magris, Martina; Cardozo, Gabriela; Santi, Francesco; Devigili, Alessandro; Pilastro, Andrea
Abstract : Several factors are involved in determining the outcome of sperm competition. In addition to sperm number, sperm quality and male phenotype, insemination order is often associated with skewed paternity share. Patterns of sperm precedence can be produced by the mechanics of sperm storage and fertilization, or by active processes under male or female control. However, as males and females always interact during copulation, it is difficult to identify the mechanism responsible. The Trinidadian guppy, Poecilia reticulata, is a polyandric species characterized by last-male sperm precedence in natural matings. During such matings, females allow attractive males to inseminate more sperm by controlling copulation duration. We used artificial insemination to clarify the extent to which female control of sperm transfer influences the observed pattern of sperm precedence in this species. This technique allowed us to experimentally manipulate the number of sperm transferred and the timing of insemination. We found a significant first-male fertilization advantage. This advantage, however, declined as the time between insemination and parturition increased. Presumably, the anatomy and the physiology of the female genital tract favour egg fertilization by the first ejaculate inseminated, whereas sperm mixing is likely to be responsible for the reduction in first-male advantage associated with longer insemination–parturition intervals. Our results suggest that the last-male precedence detected after two consecutive natural matings is caused by cryptic female preference for attractive males associated with a female trading-up strategy (i.e. the second male is more frequently more attractive than the first male), rather than by insemination order per se. As the pattern of sperm precedence has important consequences for male reproductive strategies (for example mate guarding and male mate choice copying), unravelling its dynamic represents an important contribution to understanding the sexual behaviour of this model species. Highlights: Insemination order affects the outcome of sperm competition. Artificial insemination highlights first-male sperm precedence. The mechanics of storage and fertilization are likely to be responsible for FMP. FMP is reduced as insemination-parturition interval increases. Last-male precedence in natural matings is produced by female-mediated processes.